Risk factors for bloodstream infection and predictors of prognosis in rectal carriers of carbapenem-resistant Klebsiella pneumoniae - Miaomiao Wu; Danhong Yang; Xi Li; Yicheng Huang; Hongying Pan (BMC Infectious Diseases)
Abstract Background The mortality rate of secondary bloodstream infection (BSI) derived from the intestinal colonization of carbapenem-resistant Klebsiella pneumoniae (CRKP) is extremely high. This investigation aimed at clarifying the risk factors and prognosis of BSIs resulting from the initial colonisation of CRKP. Methods In this retrospective, cross-sectional study, we analyzed the clinical data of 167 patients with CRKP colonization who received active screening during hospitalization at Zhejiang Provincial People’s Hospital from January 2019 to December 2021. The cohort consisted of 34 patients with BSI (CRKP BSI group) and 133 patients without BSI (No-BSI CRKP group).Logistic regression was employed to identify risk factors for progression from CRKP intestinal colonization to secondary BSI.Cox proportional hazards regression models were used to analyze independent risk factors for 28-day crude mortality from CRKP BSI. Results Multivariable analysis revealed that previous use of carbapenems (odds ratio [OR]:4.14, 95% confidence interval [CI]: 1.07–16.0, P = 0.040), corticosteroid use (OR: 3.18, 95% CI: 1.16–8.74, P = 0.025), and agranulocytosis (OR: 7.54, 95% CI: 2.09–27.2; P = 0.002) were independent risk factors for BSI in patients with CRKP rectal colonization. The overall mortality rate for CRKP infection was 20.4% (34/167), and the crude 28-day mortality rate for CRKP BSI was 44.1% (15/34), which was independently associated with hematologic neoplasms (P < 0.001). Among the 11 genotypically evaluated CRKP strains, 10 harbored the bla KPC−2 gene. Conclusions Neutrophil deficiency, previous use of carbapenems, and corticosteroid use are risk factors for BSI following CRKP colonization. Patients with hematologic neoplasms associated with CRKP infection are at high risk of death. Patients with clinical risk factors should be identified early, and targeted intervention measures should be taken to optimize antibiotic use and reduce the risk of subsequent BSI.